Electronic Evidence in The Healthy Justice System: Reimagined - Rita Komalasari; Cecep Mustafa (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
This study addresses one of the critical difficulties related to the admissibility of electronic evidence. This essay examines the reliability of electronic evidence in foreign criminal and civil justice systems and offers suggestions for revising the reliability of electronic evidence in Indonesian court processes. In terms of the legitimacy of electronic evidence in the criminal justice system, the method adopted is the present comparative policy approach in various nations. The paper presents the concept of a rapid check mechanism for verifying electronic evidence, which swiftly advances the settlement of criminal and civil cases.